2020
DOI: 10.1038/s41431-020-0619-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing in ADHD trios from single and multi-incident families implicates new candidate genes and highlights polygenic transmission

Abstract: Several types of genetic alterations occurring at numerous loci have been described in attention deficit hyperactivity disorder (ADHD). However, the role of rare single nucleotide variants (SNVs) remains under investigated. Here, we sought to identify rare SNVs with predicted deleterious effect that may contribute to ADHD risk. We chose to study ADHD families (including multi-incident) from a population with a high rate of consanguinity in which genetic risk factors tend to accumulate and therefore increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…We detected 9 Hi-C coupled gene-neuron associations in male suicidality GEWIS ( Table S18 ). Two of these have been previously associated with psychopathology: UBE2E3 -neuron ( z a = 4.25, p a = 1.07 × 10 −5 , z int = 4.42, p int = 4.89 × 10 −6 ) previously associated with bipolar disorder, smoking behavior, and hurt ( McCarthy et al, 2014 ) feelings; MORC3 -neuron ( z a = 4.16, p a = 1.58 × 10 −5 , z int = 4.42, p int = 4.99 × 10 −6 ) previously associated with frequency of tiredness and depressive symptoms; and DOP1B -neuron ( z a = 4.16, p a = 1.58 × 10 −5 , z int = 4.42, p int = 4.99 × 10 −6 ) previously implicated in neurological disorders and dystonias ( Al-Mubarak et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We detected 9 Hi-C coupled gene-neuron associations in male suicidality GEWIS ( Table S18 ). Two of these have been previously associated with psychopathology: UBE2E3 -neuron ( z a = 4.25, p a = 1.07 × 10 −5 , z int = 4.42, p int = 4.89 × 10 −6 ) previously associated with bipolar disorder, smoking behavior, and hurt ( McCarthy et al, 2014 ) feelings; MORC3 -neuron ( z a = 4.16, p a = 1.58 × 10 −5 , z int = 4.42, p int = 4.99 × 10 −6 ) previously associated with frequency of tiredness and depressive symptoms; and DOP1B -neuron ( z a = 4.16, p a = 1.58 × 10 −5 , z int = 4.42, p int = 4.99 × 10 −6 ) previously implicated in neurological disorders and dystonias ( Al-Mubarak et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the significant genetic correlations between ADHD and certain somatic traits or diseases (such as weight and weight-related traits, smoking-related cancer, and reproductive traits) reveal a great degree of overlap between the genetic risk factors (Demontis et al, 2019). At this point, it is important to mention that current results support that non-coding variants, such as intronic indels, have been shown to play an important role (Liu et al, 2021) not only in identifying ADHD risk genes (Al-Mubarak et al, 2020), but also for medical diseases (Tan, 2020), as the non-coding elements can regulate the transcription and translation of protein-coding genes. Consistently, recent recommendations for complex, neurodevelopmental disorders increasingly raise the usefulness of whole genome analysis, since the identification of the underlying genetic etiology between neurodevelopmental and somatic conditions can provide a more precise clinical management impacting patient care.…”
Section: Therapeutic Aspectsmentioning
confidence: 66%
“…For example, Farrer et al identified three independent loci on chromosomes 9, 10, and 12 determining Alzheimer's disease in an Israeli–Arab community with a high consanguinity rate and a familial structure resembling the one found in Sudanese families ( 26 ). Moreover, Al-Mubarak et al found at least two likely pathogenic variants in the majority of probands with attention deficit hyperactivity disorder (ADHD) in Saudi Arabia, leading to the conclusion that ADHD should be considered as a complex disorder ( 27 ).…”
Section: Discussionmentioning
confidence: 99%